Multidisciplinary management of a mandibular buccal plate perforation - Yuli Nugraeni; Chiquita Prahasanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Endodontists often have difficulty in the management of endo-perio cases, because they cannot visually detect the condition of outer root surfaces, especially in bucco-lateral roots. The bone defect is rare and its treatment needs collaboration of endodontists and periodontists. An endodontist treats cases based on dental history, radiograph of root canals to measure root canals, to uncover abnormalities and to diagnose, but as the endodontists cannot directly see the affected parts, the unseen portion of the tooth could only be seen after flap surgery. Purpose: This case presents the importance of multidisciplinary approach by the endodontist and periodontitis to treat bucal plate perforations in endo-perio cases. Case: The first patient, a 47-year-old female had endodontic treatment and a porcelain crown restoration; however, after several months she felt pain. The second patient, a 45 year-old female had endodontic treatment and after six months she feel painful. Case management: The first patient, was referred to a periodontist. The opening flap surgery has been done, a bone defect was found in tooth 45. Subsequently, the exposed crater was filled with a bone graft and the pain disappeared. The second patient, with improper endodontic treatment. The flap surgery was conducted, there was found a bone defect in tooth 36. The last treatment, a bone graft has been covered and then the pain was not present. Conclusion: Proper diagnosis and treatment of perforations on the buccal aspect of a root was able to eliminate pain and avoid tooth extraction.Latar belakang: Endodontis sering mengalami kesulitan dalam menangani kasus endo-perio karena secara visual kondisi ini tidak tampak diluar permukaan akar, khususnya pada akar bukolateral. Defek tulang sangatlah jarang dan perawatannya membutuhkan kolaborasi endodotis dan periodontis. Seorang endodontis merawat kasus-kasus berdasarkan riwayat gigi, radiografis saluran akar untuk melihat saluran akar, melihat abnormalitas dan diagnosis, tetapi ketika endodontis tidak dapat secara langsung melihat bagian yang terlibat, bagian gigi yang tidak terlihat ini hanya dapat dilihat setelah dilakukan bedah flap. Tujuan: Kasus ini menunjukkan pentingnya pendekatan multidisipliner oleh endodontis dan periodontis dalam menangani perforasi aspek bukal akar pada kasus endoperio. Kasus: Pasien pertama, seorang wanita 47 tahun telah mendapatkan perawatan endodontik dan restorasi mahkota porselen, akan tetapi selama beberapa bulan pasien tersebut mengeluh nyeri. Pasien kedua, seorang wanita 45 tahun telah mendapatkan perawatan endodontik dan setelah 6 bulan juga mengeluh nyeri pada gigi tersebut. Tatalaksana kasus: Pasien pertama dirujuk ke periodontis. Bedah pembukaan flap dilakukan dan ditemukan defek tulang pada gigi 45, kemudian crater yang terbuka diisi graft tulang dan nyeri berangsur hilang. Pada pasien kedua ditemukan perawatan endodontik yang kurang baik. Pada pasien ini ilakukan bedah flap dan ditemukan defek tulang pada gigi 36, pada akhir perawatan graft tulang dipasang dan nyeri berangsur hilang. Kesimpulan: Diagnosa dan perawatan perforasi yang tepat pada aspek bukal akar dapat menghilangkan nyeri dan menghindari ekstraksi gigi.